2020
DOI: 10.3892/ol.2020.12173
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA SNHG5 promotes cell proliferation, migration and invasion in oral squamous cell carcinoma by sponging miR‑655‑3p/FZD4 axis

Abstract: Recently, previous studies have shown that long non-coding RNA (lncRNA) can act as a tumor promoter or inhibitor in the pathogenesis of oral squamous cell carcinoma (OSCC). However, the regulatory mechanism of lncRNA SNHG5 is unknown in OSCC. Therefore, the functional mechanism of lncRNA SNHG5 in OSCC was initially revealed in this study. Here, RT-qPCR and western blot analysis were used to assess mRNA and protein expression. The functional mechanism of SNHG5 was investigated by MTT, Transwell and luciferase r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Despite the fact that Transwell and wound healing studies in vitro demonstrated that SNHG5 inhibited migration and invasion of LAD cells, MTS testing revealed no difference in A549 cell proliferation. Therefore, additional research is needed to understand the essential functions of SNHG5 in human cancer [ 33 ]. However, the negative correlation between SNHG5 and several valuable prognostic biomarkers for LAD, including CEA, NSE, and MASP2, and the increased expression of SNHG5 mRNA induced by cisplatin in the previous strongly suggest that SNHG5 might have a therapeutic role in LAD [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that Transwell and wound healing studies in vitro demonstrated that SNHG5 inhibited migration and invasion of LAD cells, MTS testing revealed no difference in A549 cell proliferation. Therefore, additional research is needed to understand the essential functions of SNHG5 in human cancer [ 33 ]. However, the negative correlation between SNHG5 and several valuable prognostic biomarkers for LAD, including CEA, NSE, and MASP2, and the increased expression of SNHG5 mRNA induced by cisplatin in the previous strongly suggest that SNHG5 might have a therapeutic role in LAD [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that lncRNAs are new diagnostic and prognostic biomarkers for various tumors including LUAD [ 9 , 11–15 , 43 , 44 ], and a high expression of the lncRNA EBLN3P is associated with tumor progression [ 16 , 17 , 45 ]. Xu et al indicated that lncRNA EBLN3P promotes colorectal cancer progression by sponging miR-323a-3p [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent study has shown that exosome-carried miR-655-3p is down-regulated in plasma of patients with PTC compared with the healthy group (Liang et al, 2020). MiR-655-3p, an important component for the regulatory network of microRNAs, is identified as a tumor suppressor in multiple cancers, including lung cancer (Wang et al, 2019a), hepatocellular carcinoma (Wu et al, 2016), and oral squamous cell carcinoma (Yu et al, 2020). However, the function and molecular mechanism of exosomal miR-655-3p in PTC have not been reported.…”
Section: Introductionmentioning
confidence: 99%